2021
DOI: 10.1037/pro0000366
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapist as a secure base figure: Validation of the Secure Base Questionnaire (SBQ).

Abstract: This article describes the validation of a new measure for evaluating psychotherapists' relational dimensions. The Secure Base Questionnaire (SBQ) is a self-report measure designed to assess how psychotherapists perceive themselves as a secure base for their clients. The provision of a secure base in psychotherapy consists of the therapist's ability to be consistently responsive and emotionally available, and to provide conditions for the exploration and review of the client's internal working models of self a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…They found that the therapist's selfreported romantic attachment was associated with distinct representations of care and the client's needs in therapy. Insecure dimensions of attachment, such as dependence and ambivalence, were associated with more insecure patterns of secure base provision, namely with a higher prevalence of compulsive caregiving behaviors and more difficulties regarding tolerance for uncertainty in the psychotherapeutic process (Carvalho & Matos, 2021). Both of these studies provide additional proof of the therapist's attachment role when facing more self-challenging experiences in psychotherapy.…”
Section: Therapists As Secure Base Figuresmentioning
confidence: 75%
See 4 more Smart Citations
“…They found that the therapist's selfreported romantic attachment was associated with distinct representations of care and the client's needs in therapy. Insecure dimensions of attachment, such as dependence and ambivalence, were associated with more insecure patterns of secure base provision, namely with a higher prevalence of compulsive caregiving behaviors and more difficulties regarding tolerance for uncertainty in the psychotherapeutic process (Carvalho & Matos, 2021). Both of these studies provide additional proof of the therapist's attachment role when facing more self-challenging experiences in psychotherapy.…”
Section: Therapists As Secure Base Figuresmentioning
confidence: 75%
“…In another study, Carvalho and Matos (2021) also presented the development of a self-report questionnaire for psychotherapists' ratings of secure base behaviors in psychotherapy in four distinctive dimensions [Secure Base Questionnaire (SBQ) -sen-sitivity, encouragement of exploration, compulsive caregiving, and avoidance of uncertainty]. They found that the therapist's selfreported romantic attachment was associated with distinct representations of care and the client's needs in therapy.…”
Section: Therapists As Secure Base Figuresmentioning
confidence: 99%
See 3 more Smart Citations